People and planet over profits : (Asia Pacific Research Network, 2008)
The objective of this book is to provide focal point on the issues of climate change, environment and natural rasources region. This also serves our preparation for engagement in various processes including the Bali Conference of Parties of the UN FCCC, as well as planning of the natural resources stream of APRN members.